How does birth order influence full immunization coverage among children aged 12–23 months in India? evidence from the National Family Health Survey - Tanmoy Ghosh; Puja Das; Apurba Sarkar; Pradip Chouhan (PLoS ONE, 2026)
Despite the availability of free basic vaccination programmes, the disparity continues in immunization coverage among children aged 12–23 months in India, particularly with increasing birth orders. Using the data from the NFHS 5 (2019–21), the study seeks to investigate how birth order affects the likelihood of children’s immunization aged 12–23 months in India. The analysis included a nationally representative sample of 43,436 children aged 12–23 months. Bivariate LISA and multilevel logistic regression models were performed to assess spatial and statistical patterns. The study found that spatial autocorrelation analysis indicated a positive association between 1st and 2nd birth orders and child full immunization coverage. However, the likelihood of full immunization declines significantly with increasing birth order [2 nd (OR: 0.91); 3 rd (OR: 0.74); 4 th (OR: 0.64); 5 th (OR: 0.56); 6 and more (OR: 0.41)]. Similarly, other socio-demographic covariates such as female children [AOR: 0.95], children who belong to Muslim families [AOR: 0.72], and resided in the northeastern part [AOR: 0.52] of India had a lower likelihood of being completely immunized. Therefore, the present study underscores the urgent need for targeted public health interventions that address both familial and structural barriers to immunization, specifically for mothers who have more than two children, to ensure that no child is left behind, regardless of their birth position within the family.